Triadic Analysis of Students' Self-Regulated Learning as a Response to Learning Support of Environmental Science Course - Wachju Subchan; Nurul Umamah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Self-Regulated Learning (SRL) reflects the development of learning independence, self-regulation in learning, self-management ability in the learning process, and the students' ability to manage learning experiences to obtain optimal learning outcomes. The development of SRL is a process of encouraging students' activity to foster the cognition and behavior aspects that demand systematic self-regulation to achieve the learners' learning goals. Thus, reflecting on students' SRL becomes an essential and strategic aspect of being explored and developed in learning management because it is fundamental to learning success. There are three main components that must be measured, namely self, environmental, and behavior. Each of the indicators of the three components interacts with each other. The analysis of the three components (triadic analysis) in order to develop students' SRL is a very urgent aspect for educators. This study aims to conduct a triadic analysis of students' SRL in response to the learning support of the Environmental science course. The population of this study is students of 3 courses, namely: Environmental Knowledge (Biology Education Study Program), Environmental Education (History Education Study Program) of the Faculty of Teacher Training and Education, and Environmental Sciences (History Study Program) of Faculty of Cultural Sciences, University of Jember. The sample of this study was students who took the course and filled out the SRL's questionnaire in the form of a Google form distributed through social media, Whatsapp (WA). The result of this study shows that the condition of the learning environment that students respond to in the form of environmental self-regulation is on a positive average in the range above 80%. Likewise, the students' self-planning, self-efficacy, and self-evaluation responses are reflected in the form of self-regulation behavior in good condition (in the range above 80%). However, in the self-evaluation indicators, some students are inconsistent in self-planning and self-efficacy, which leads to non-achievement of the targets set.